Silicon-based Nanomaterials - Li, Handong; Wu, Jiang; Wang, Zhiming M. (Springer Series in Materials Science,, 2013)
A variety of nanomaterials have excellent optoelectronic and electronic properties for novel device applications. At the same time, and with advances in silicon integrated circuit (IC) techniques, compatible Si-based nanomaterials hold promise of applying the advantages of nanomaterials to the conventional IC industry. This book focuses not only on silicon nanomaterials, but also summarizes up-to-date developments in the integration of non-silicon nanomaterials on silicon. The book showcases the work of leading researchers from around the world who address such key questions as: Which silicon nanomaterials can give the desired optical, electrical, and structural properties, and how are they prepared? What nanomaterials can be integrated on to a silicon substrate and how is this accomplished? What Si-based nanomaterials may bring a breakthrough in this field? These questions address the practical issues associated with the development of nanomaterial-based devices in applications areas such as solar cells, luminous devices for optical communication (detectors, lasers), and high mobility transistors. Investigation of silicon-based nanostructures is of great importance to make full use of nanomaterials for device applications. Readers will receive a comprehensive view of Si-based nanomaterials, which will hopefully stimulate interest in developing novel nanostructures or techniques to satisfy the requirements of high performance device applications. The goal is to make nanomaterials the main constituents of the high performance devices of the future. Describes today's most promising approach to the full use of nanomaterials in device applications Provides the keys to understanding the integration of nanomaterials with silicon ICs Addresses both materials growth and properties Covers both silicon and non-silicon nanomaterials Written by leading experts in each research area.